ICJ Jurisdiction Over the Case of Policy to Stop Nickel Exports: European Union v. Indonesia - Gunawan, Yordan; Amirullah, Muhammad Nur Rifqi; Arumbinang, Mohammad Hazyar (Faculty of Law, Jambi University, 2023)
The purpose of this paper is to explore the jurisdiction of the International Court of Justice (ICJ) regarding the European Union's legal action against Indonesia in response to Indonesia's policy to halt the export of raw materials derived from nickel ore. The research methodology employed for this paper is normative legal research, relying primarily on legal materials that encompass normative law for data collection. The outcome of this study indicates that Indonesia has implemented a measure to cease the export of raw materials derived from nickel ore, leading to the domestic downstream management of mineral resources within the country. In addition, the purpose of the export stop is the strong desire of the Indonesian government so that all raw materials are managed domestically and can invite investors from abroad to invest in Indonesia. However, the European Union (EU), as one of the enthusiasts and consumers of nickel ore raw materials, objected to the policy issued by Indonesia. The form of objection from the EU is to sue Indonesia to the WTO. The EU objected to the policies issued by the Indonesian government because they could interfere with various policies taken by the EU. The policy is expected that in 2050 the EU will be free from CO2 emissions. Furthermore, the EU argues that the cost of nickel ore, once domestically managed, is anticipated to undergo a significant increase, surpassing the prevailing market price. The author scrutinizes the jurisdictional aspects regulated by the International Court of Justice (ICJ) within this context